2016
DOI: 10.2139/ssrn.2797215
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy Rules in Emerging Countries: Is There an Augmented Nonlinear Taylor Rule?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 16 publications
(37 reference statements)
1
24
0
Order By: Relevance
“…Further dimensions to the Taylor rule such as the smoothing of interest (Blinder & Reis, 2005) and the fact that policymakers react to future macroeconomic developments (Woodford, 2001) enriched the policy rule discourse. The nonlinear policy rule paradigm (Ahmad, 2016;Caporale, Helmi, Çatık, Ali, & Akdeniz, 2018;Liu, Xu, Zhao, & Song, 2018) raised serious doubts about the linear Taylor rule and ushered in a new strand of the policy rule literature. However, what is fundamentally missing in all of these is the constraint that high debt levels pose to monetary policymakers in the very response that these previous studies sought to capture.…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Further dimensions to the Taylor rule such as the smoothing of interest (Blinder & Reis, 2005) and the fact that policymakers react to future macroeconomic developments (Woodford, 2001) enriched the policy rule discourse. The nonlinear policy rule paradigm (Ahmad, 2016;Caporale, Helmi, Çatık, Ali, & Akdeniz, 2018;Liu, Xu, Zhao, & Song, 2018) raised serious doubts about the linear Taylor rule and ushered in a new strand of the policy rule literature. However, what is fundamentally missing in all of these is the constraint that high debt levels pose to monetary policymakers in the very response that these previous studies sought to capture.…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
“…The STAMP undertakes the decomposition with the aid of the maximum likelihood estimation technique. Earlier studies such as Liu et al (2018), Caporale et al (2018) and Ma (2016) had employed the Hodrick-Prescott (HP) filter developed by Hodrick and Prescott (1997) to estimate the trend. The HP filter, however, exhibits some limitations.…”
Section: Output Gapmentioning
confidence: 99%
“…Evidence can be found that the euro/dollar exchange rate follows its short-term interest differential. For the EMEs, according to Caporale et al (2018), such an exchange rate augmented Taylor rule is requested to describe their interest rate setting. As our sample includes countries with fairly stable exchange rates and others with more volatile rates, we expect that the coefficient of the exchange rate in the monetary policy equation will be heterogeneous across countries.…”
Section: On Output Development and The Currency Valuementioning
confidence: 99%
“…Bec, Salem, and Collard (2002), Cukierman and Gerlach (2003), Nobay and Peel (2003), Ruge-Murcia (2004), Martin and Milas 2004, Kim, Osborn, and Sensier (2005), Taylor and Davradakis (2006), and Surico (2007aSurico ( , 2007b, Petersen (2007), Cukierman and Muscatelli (2008), Hayat and Mishra (2010), and Castro (2011) also argue that the Taylor rule could be better specified as a non-linear relationship if central banks have asymmetric responses to positive and negative deviations in the inflation and output gap. Caporale et al (2016) estimates a Threshold Autoregressive (TAR), exchange rate-augmented Taylor rule specification for five inflation targeting, emerging countries and find substantial evidence for non-linearity in the conduct of monetary policy. In addition, they also find that most of the central banks react to deviations in real exchange rates.…”
Section: Review Of Literaturementioning
confidence: 99%